Problematika Pelaksanaan Pembelajaran Matematika Berbasis Kurikulum 2013(Studi kasus pada siswa kelas VIII di SMP Negeri 2 Blora) - Yandita Riskadini, Winda; , Muhammad Noor Kholid, S.Pd.,M.Pd (2016)
This study aimed to describe the problems faced by teachers prior to the learning process, the learning process after the learning process of mathematics based on the National Curriculum SMP Negeri 2 Blora. This research is a qualitative research. The subjects were three math teachers who teach in class VIII N 2 Blora and five students of class VIII SMP 2 Blora, selected by purposive sampling. Data collection techniques in this research is participant observation, semi-structured interviews and document study. Data analysis was performed periodically during and after the collection of data through three stages, namely: (1) data reduction, (2) presentation of data, and (3) conclusion and verification. Mechanical data validity checking is done by triangulation techniques and triangulation of sources. The results were obtained in the planning of teacher learning proses` sometimes do not make the lesson plan before teaching process. RPP found in the material component not explained by category, facts, concepts, principles and procedures. RPP components are made basically the same format as the RPP on Curriculum 2006, only the Curriculum 2006 core competencies there is no. In the implementation of learning problems it found that teachers due to lack of fulfillment of textbook-based Curriculum 2013, these problems are also felt by students. In the implementation of assessments by teachers are not many obstacles, because the judgment easier and easier for students to obtain better value. Keywords: Curriculum 2013, Problematics of Learning